The Apollo ATCA design for the CMS track finder and the pixel readout at the HL-LHC. (1st April 2022) - Albert, A.; Demiragli, Z.; Gastler, D.; Hahn, K.; Hazen, E.; Kotamnives, P.; Noorudhin, S.; Peck, A.; Rohlf, J.; Strohman, C.; Wittich, P.; Zou, R.; et al.
Abstract: The challenging conditions of the High-Luminosity LHC require tailored hardware designs for the trigger and data acquisition systems. The Apollo platform features a "Service Module" with a powerful system-on-module computer that provides standard ATCA communications and application-specific "Command Modules" with large FPGAs and high speed optical fiber links. The CMS version of Apollo will be used for the track finder and the pixel readout. It features up to two large FPGAs and more than 100 optical links with speeds up to 25 Gb/s. We study carefully the design and performance of the board by using customized firmware to test power consumption, heat dissipation, and optical link integrity. This paper presents the results of these performance tests, design updates, and future plans.